2021
DOI: 10.3389/fcell.2021.662805
|View full text |Cite
|
Sign up to set email alerts
|

Theileria’s Strategies and Effector Mechanisms for Host Cell Transformation: From Invasion to Immortalization

Abstract: One of the first events that follows invasion of leukocytes by Theileria sporozoites is the destruction of the surrounding host cell membrane and the rapid association of the intracellular parasite with host microtubules. This is essential for the parasite to establish its niche within the cytoplasm of the invaded leukocyte and sets Theileria spp. apart from other members of the apicomplexan phylum such as Toxoplasma gondii and Plasmodium spp., which reside within the confines of a host-derived parasitophorous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 128 publications
0
24
0
Order By: Relevance
“…Theileria spp. contain microspheres, equivalent to the dense granules of T. gondii, during the sporozoite phase but not the schizont phase [ 39 ]. It is unclear whether these are present during the piroplasm phase [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Theileria spp. contain microspheres, equivalent to the dense granules of T. gondii, during the sporozoite phase but not the schizont phase [ 39 ]. It is unclear whether these are present during the piroplasm phase [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This role supposedly might be played by the newly identified Babesia ASP3b isoenzyme. Similarly, Theileria's surface coat is shed by an undescribed protease, suggesting an identical role of the Theileria ASP3b orthologues [62]. Initial attachment of the parasite to the host erythrocyte is followed by the reorientation of the apical tip towards the host cell, and the establishment of the moving (tight) junction (MJ) [63].…”
Section: Clade Cmentioning
confidence: 99%
“…Both Plasmodium and Toxoplasma use sophisticated protein transporting complexes PTEX (plasmodium translocon of exported proteins) and the MYR translocon, respectively, which are incorporated into the PVM [92,93]. Unsurprisingly, piroplasms do not encode for components of the Plasmodium translocon machinery [29], with the single exception of the PTEX complex protein component HSP101, which is expressed across all piroplasms [62].…”
Section: Clade Dmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that Theileria parva and Theileria annulata , which are also known as transforming species, are highly pathogenic species for cattle. Other species of Theileria that infect cattle, Theileria mutans , Theileria taurotragi , and members of the Theileria orientalis complex, frequently cause benign infections [ 3 , 4 , 5 ]. It has been observed that Theileria orientalis , long thought to be benign, has different genotypes, some of which cause clinical cases and adversely affect the cattle industry [ 6 ].…”
Section: Introductionmentioning
confidence: 99%